Measurement of residual stresses in titanium alloys using synchrotron radiation. (July 2019) - Umapathi, A.; Swaroop, S.
Highlights: Laser peening without coating (LPwC) was done on titanium alloys TC6 and Ti-6Al-4V. Power density and number of passes were varied. Residual stresses measured by quick and effective angle dispersive synchrotron radiation. The efficacy of the above measurement is discussed in detail. Abstract: The residual stress distribution due to laser peening without coating (LPwC) was measured by using the synchrotron radiation X-rays from BL-11 at INDUS-2, RRCAT, Indore, India. This was accomplished by using the effective and quick method of angle-dispersive X-ray diffraction (AD-XRD). LPwC was performed on the titanium TC6 and Ti-6Al-4V alloys with a laser wavelength of 1064 and 532 nm and samples were peened with three different laser power densities of 3, 6 and 9 GW cm −2 and subjected to multiple impacts (1/3/5). Followed by that, the residual stress measurements using synchrotron radiation beam energy (SRBE) of 20 and 30 keV were carried out. The results show that LPwC induces higher and deep residual stress depending upon the titanium alloy. The change of residual stress with laser power densities and impact times are calculated and discussed. Although a compressive residual stress (CRS) was observed in majority of the cases, the more detrimental tensile residual stress (TRS) was observed in few cases only, especially with the TC6 alloy. TC6 showed TRS with peening radiations of 532 nm (power density of 3 GW cm −2 ) and 1064 nm (power density of 9 GW cm −2 ). Besides, TRS was observed in multiple peened samples (5 times) at both radiations. In each of the instances the residual stress was measured at SRBE of 20 keV. It is suggested that for beneficial CRS, peening may be employed in conditions other than these.